خوشنودئ سلاطین کے لیے فتنہ وضعِ حدیث؛ ایک تجزیاتی مطالعہ: The Menace of Fabricating Hadith for the Pleasure of Rulers (An Analytical Study) - Ubaidullah, Dr. Muhammad; Raza, Muhammad Irfan; Bodla, Muhammad Abdullah (Al-Amīr Research Journal for Islamic Studies, 2023)
The proliferation of fabricated Hadiths, particularly those concocted to serve the interests of rulers and the affluent, represents a significant challenge to the integrity of Islamic teachings. This article delves into the phenomenon of crafting and disseminating false Hadiths to appease or legitimize the actions of monarchs and wealthy elites throughout Islamic history. It examines the motivations behind such fabrications, the methods employed to expose and counter them, and the broader implications for the authenticity of Hadith literature. By analyzing historical instances where fabricated Hadiths were used as tools of political or social influence, the article underscores the vigilant efforts of Islamic scholars in safeguarding the Hadith corpus from corruption. It highlights the stringent criteria developed by Hadith scholars for the verification and validation of Hadiths, demonstrating the Islamic scholarly community’s commitment to preserving the Prophet Muhammad’s (Peace be upon him) teachings in their pristine form. Furthermore, the article discusses the ethical and theological ramifications of attributing false statements to the Prophet Muhammad (Peace be upon him), emphasizing the condemnation of such acts within Islamic jurisprudence. It reflects on the enduring relevance of these issues in contemporary times, especially in the context of misinformation and the misuse of religious texts for personal or political gain. In this article, we explore the grave issue of fabricating Hadiths in the context of seeking favor and status among rulers and the affluent, a practice that has marred the purity of Islamic teachings throughout history. We delve into the motivations behind such acts, highlighting how individuals, driven by the desire for political gain, social standing, or financial benefits, resorted to attributing false statements to Prophet Muhammad (Peace be upon him). The consequences of these actions are scrutinized, shedding light on the distortion of Islamic jurisprudence and the confusion it caused among Muslim communities. Key Words: Hadith, Fabrication, False Narration, proliferation Pleasure of Rulers.